Effect of the dwell time deviation constraint on brachytherapy treatment planning for cervical cancer. Issue 8 (August 2021) - Yan, Gaoshu; Kang, Shengwei; Tang, Bin; Li, Jie; Wang, Pei; Wang, Xianliang; Lang, Jinyi
Objective: This study aimed to quantify the effect of the dwell time deviation constraint (DTDC) on brachytherapy treatment for cervical cancer. Methods: A retrospective study was carried out on 20 patients with radical cervical cancer. The DTDC values changed from 0.0 to 1.0 by a step size of 0.2. We adjusted the optimization objectives to ensure that all plans were optimized to a high-risk clinical target volume (HRCTV) D 90 (the dose to 90% of the HRCTV) = 6 Gy, while keeping the dose to the organs at risk as low as possible. The dose–volume histogram parameters and the dwell time data were compared between plans with different DTDC values. Results: The HRCTV volume covered by 150% of the prescription dose gradually increased with increasing DTDC values. As the DTDC value increased from 0.0 to 1.0, the effective dwell point proportion increased from 61.78% to 90.30%. The mean dwell time initially decreased with an increase in the DTDC value, reached the minimum value at DTDC = 0.8, then slightly increased at DTDC = 1.0. Conclusions: When using inverse planning simulated annealing optimization for radical cervical cancer cases, the recommended DTDC value is approximately 0.6 if the organ dose needs to be limited.